Ethics and Natural Science through Paul Ricoeur’s Hermeneutics - Vodicar, Janez (Communications - Scientific letters of the University of Zilina, 2017)
Paul Ricoeur‘s well-known perspective on philosophical hermeneutics could also be applied in the understanding of natural sciences. This should resemble dialectic between explanation and understanding, which would enable the kind of objectivity that is claimed in all areas of science. Therefore, science could be viewed as an epistemological activity focused on modeling and confirmation of theory, as well as a theoretical practice that operates alongside other technological, ethical, and political practices. From epistemological perspective we will look for a role of hermeneutics in natural science. Explanation and understanding connect natural science with hermeneutics. Through a narrative position of Ricoeur’s hermeneutics, we can understand the connection between science and its responsibility.